Remote sensing of mountain snow from space: status and recommendations - Gascoin, Simon; Luojus, Kari; Nagler, Thomas; Lievens, Hans; Masiokas, Mariano; Jonas, Tobias; Zheng, Zhaojun; De Rosnay, Patricia (Frontiers in Earth Science, 2024)
The spatial and temporal variation of the seasonal snowpack in mountain regions is recognized as a clear knowledge gap for climate, ecology and water resources applications. Here, we identify three salient topics where recent developments in snow remote sensing and data assimilation can lead to significant progress: snow water equivalent, high resolution snow-covered area and long term snow cover observations including snow albedo. These topics can be addressed in the near future with institutional support.